Do contented customers make shareholders wealthy? Implications of intangibles for security pricing - Erik Theissen; Lukas Zimmermann (University of Cologne, Centre for Financial Research (CFR), 2020)
We explore the relation between customer satisfaction and security returns. Firms with high customer satisfaction levels earn significant abnormal returns. This result is robust to variations of model specification and test methodology. Additional tests do not reveal evidence of systematic mispricing. Our results rather suggest that there are, consistent with the model of Eisfeldt and Papanikolaou (2013), sources of risk not covered by standard risk factors. We identify firm characteristics, such as the Hoberget al. (2014) product market fluidity measure, and macro variables, such as patenting activity and aggregate R&D spending, that are related to these sources of risk.
Keywords: E22; G12; G14; M31; 330; Intangible Capital; Customer Satisfaction; Innovativity; ESG-Investing